1996
DOI: 10.1152/jn.1996.75.6.2334
|View full text |Cite
|
Sign up to set email alerts
|

Unified theory regarding A/P and M/L balance in quiet stance

Abstract: 1. Control of posture in quiet stance has been quantified by center of pressure (COP) changes in the anterior-posterior (A/P) and medial-lateral (M/L) directions from a single force platform. Recording from a single force platform, researchers are unable to recognize two separate mechanisms that become evident when two force platforms are used. Depending on the stance position taken, many combinations of an ankle mechanism and a hip (load/unload) mechanism are evident. In side-by-side stance, A/P balance is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

46
698
3
39

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 974 publications
(786 citation statements)
references
References 9 publications
46
698
3
39
Order By: Relevance
“…Similarly to the current study, some authors demonstrated greater displacement in the anterior-posterior direction in COPD patients 3 ; however, Rocco et al 22 observed increased lateral center of pressure displacement (but no increased anterior-posterior center of pressure displacement) compared to healthy controls. Interestingly, balance in the lateral direction is primarily maintained by torques at the trunk muscles and movement, whereas anterior-posterior direction is primarily maintained by torques at the ankle 23 . Despite not having a control group, our study suggests that lateral imbalance in adults with CF may also be due to a marked impairment in respiratory muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to the current study, some authors demonstrated greater displacement in the anterior-posterior direction in COPD patients 3 ; however, Rocco et al 22 observed increased lateral center of pressure displacement (but no increased anterior-posterior center of pressure displacement) compared to healthy controls. Interestingly, balance in the lateral direction is primarily maintained by torques at the trunk muscles and movement, whereas anterior-posterior direction is primarily maintained by torques at the ankle 23 . Despite not having a control group, our study suggests that lateral imbalance in adults with CF may also be due to a marked impairment in respiratory muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…The ankle strategy assumes that the body's COM is repositioned by moving the whole body as a single-segment, inverted pendulum, about the ankle joints, either by controlling ankle muscle stiffness or by increasing ankle muscle activity and changing the "muscle-spring" offset position (Nashner and McCollum 1985;Horak et al 1990;Winter et al 1996Winter et al , 1998Morasso and Sanguinetti 2002). The hip strategy involves antiphasic motion about both the ankle and hip joints (Nashner and McCollum 1985;Horak et al 1990;Winter et al 1996Winter et al , 1998Runge et al 1999). Extensions of these strategies include a mixed hip-ankle strategy (Kuo and Zajak 1993;Kuo 1995).…”
Section: Arm Movements and Trunk Motionmentioning
confidence: 99%
“…Recently, however, this concept has been challenged for motion occurring during quiet stance (Aramaki et al 2001;Loram and Lakie 2002). Indeed, as body motion increases in amplitude and direction from that of quiet standing (Fitzpatrick et al 1992(Fitzpatrick et al , 1994Winter et al 1996Winter et al , 1998Gatev et al 1999;Accorneo et al 1997), to that induced by a support surface perturbation in the pitch plane alone (Cordo and Nashner 1982;Allum et al 1993;Horak et al 1997), and finally to that induced by combined roll and pitch plane perturbations (Moore et al 1988;Maki et al 1994aMaki et al , 1994bHenry et al 1998b;Carpenter et al 1999;Allum et al 2002), the multi-link nature of human postural corrections becomes increasingly prominent. This multi-link strategy involves hinging at the knees, hips and lower vertebral column, in addition to ankle joint motion .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying impaired balance in COPD are poorly understood; however, mediolateral (ML) balance control appears more impaired than anteroposterior (AP) control [4]. In quiet stance, ML balance depends on hip and trunk moments/movements, whereas AP control is controlled by ankle moments/movements [5,6].…”
Section: Introductionmentioning
confidence: 99%